An investigation into the use of Israel’s “historical traditions” in Joel 1:2-20 - Redelinghuys, CJ (Stellenbosch Theological Journal, 2016)
The text of Joel 1:2-20 presents the reader with a unique, albeit challenging, perspective on an unprecedented disaster – a locust plague (and a subsequent drought) as the harbinger of the Yom YHWH (Day of the LORD). In his own unique way the author of Joel portrays this calamity by appealing to the ancient community’s knowledge of their professed historical (and theological) traditions. In particular, he distinctly emphasizes four of these traditions namely Creation, Exodus, Sinai, and Promised Land. Approaching the text in this manner, from the perspective of Israel’s historical traditions (and thus drawing on the work done by Gerhard von Rad), it is explained that the emphasis falls on a twofold textual focus (explicitly and implicitly): primarily on divine judgement, but conversely also on YHWH’s saving blessings.